2013
DOI: 10.1186/1471-2164-14-404
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity revealed by sequence analysis of Mycobacterium tuberculosis isolates from extra-pulmonary tuberculosis patients

Abstract: BackgroundTuberculosis remains a major public health problem. Clinical tuberculosis manifests often as pulmonary and occasionally as extra-pulmonary tuberculosis. The emergence of drug resistant tubercle bacilli and its association with HIV is a formidable challenge to curb the spread of tuberculosis. There have been concerted efforts by whole genome sequencing and bioinformatics analysis to identify genomic patterns and to establish a relationship between the genotype of the organism and clinical manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Moreover, a recent study showed advanced immune suppression to be associated with increased prevalence of mixed-strain MTB infection[ 36 ] which may lead to selection of the most adapted strain to be disseminated. Although not compared with concurrent pulmonary TB, EPTB has recently been found to be genotypically heterogeneous as revealed by whole genome sequence analysis [ 11 ]. A recent similar study on Mycobacterium avium complex (MAC) found high genetic diversity in strains that cause pulmonary and disseminated disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study showed advanced immune suppression to be associated with increased prevalence of mixed-strain MTB infection[ 36 ] which may lead to selection of the most adapted strain to be disseminated. Although not compared with concurrent pulmonary TB, EPTB has recently been found to be genotypically heterogeneous as revealed by whole genome sequence analysis [ 11 ]. A recent similar study on Mycobacterium avium complex (MAC) found high genetic diversity in strains that cause pulmonary and disseminated disease [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic markers that track TB transmission include IS6110, polymorphic GC-reach repetitive sequences, direct repeat regions and mycobacterial interspersed repetitive units [ 3 - 7 ]. Recently, it was shown that bacterial whole genome sequencing (WGS) provides greater discriminative power [ 8 - 11 ]. WGS of multiple isolates may address a broad range of topics – from questions on the transmission of clinical strains to how M. tuberculosis evolves over long and short time scales.…”
Section: Introductionmentioning
confidence: 99%
“… Zhang et al [ 26 ] 2013 161 Identify drug resistance genes Yes No Phylogenetics and comparison of rates with poisson distribution Yes; list of genes provided Farhat et al [ 15 ] 2013 124 Identify drug resistance genes Yes No Phylogenetics and convergence analysis Yes; list of genes provided Lin et al [ 27 ] 2013 2 Identify drug resistance genes Yes No Comparison with reference mycobacterial strains No Wu et al . [ 28 ] 2013 4 Identify Beijing associated pathways Yes No COG enrichment of genes with snps General pathways rather than individual genes Das et al [ 29 ] 2013 5 Identify genes related to extrapulmonary TB Yes No COG enrichment of genes with snps General pathways rather than individual genes Ilina et al [ 30 ] 2013 4 Identify drug resistance genes Yes No Comparison with reference mycobacterial strains No Abrahams et al [ 31 ] 2013 - Identify resistance targets(s) for novel imidazole No Yes: spontaneous mutants resistant to drug and their sensitive ancestor Identification of all mutations …”
Section: Resultsmentioning
confidence: 99%